Review of current evidence available for guiding optimal Enoxaparin prophylactic dosing strategies in obese patients—Actual Weight-based vs Fixed. (May 2017) - He, Zikai; Morrissey, Hana; Ball, Patrick
Abstract: Background: The current debate over the optimal Enoxaparin prophylactic dosing strategies in obese patients centre around whether it should be based on the actual weight of the patient (i.e. weight-based), or at an artificially fixed amount, as it is the case in Australia (40 mg daily). The vast majority of the evidence available today is laboratory-based, measuring serum Antifactor-Xa activities as a marker for physiological response. Aim: The aim of the parent study is to compare the clinical outcomes for obese patients who received fixed doses of enoxaparin compared to those who received weight-based doses within the licensed dosage recommendations. This review was conducted to examine whether a gap in knowledge exists in relation to dosing obese patients with enoxaparin as VTE prophylaxis after hospital admission to aid in development of the parent study concept. Method: Databases such as Medline, EBSCOhost, ProQuest were interrogated using combinations of words such as "enoxaparin", AND "dosing strategy", AND "obese/obesity" AND "prophylaxis". Only eleven out of 14 primary studies which were considered to be sufficiently similar in methodology and anticipated outcomes were reviewed and analysed. Results: Pooled data from the eleven studies suggested that weight-based or higher-than-fixed dosing had a 36.2% higher success rate than fixed dosing, and was more likely to achieve the desired serum Anti-Xa activity levels (52.2% and 16% respectively). The rate of failure to achieve this is significantly lower in the weight-based groups (13.3%) than in fixed-dose groups (18.5%). These eleven studies reviewed included 601 patients in total. Conclusion: There is insufficient evidence to support or negate the current enoxaparin health outcomes in obese and very obese patients due to the lack of post-discharge follow-up from hospitals. Further research is required to compare long-term outcomes after fixed and weight-based dosing of enoxaparin. The optimal dose of enoxaparin per kilogram of body weight for prophylaxis remains to be determined.